Feasibility and tolerability of moderate intensity regular physical exercise as treatment for core symptoms of attention deficit hyperactivity disorder: a randomized pilot study - Svedell, L. A.; Holmqvist, K. L.; Lindvall, M. A.; Cao, Y.; Msghina, M. (Frontiers in Sports and Active Living, 2023)
Background Attention deficit hyperactivity disorder (ADHD) is associated with sedentary lifestyle, low quality of life and low physical fitness. Studies in children with ADHD have shown that regular physical exercise can help reduce core ADHD symptoms, but evidence for this is lacking in adults. Although guidelines recommend multi-modal treatment, central stimulants (CS) remain the mainstay of treatment. CS are effective in the short-term, but their long-term efficacy remains to be established. There is thus huge unmet need for developing non-pharmacological treatment options, and for well-designed randomized controlled trials (RCTs). Objective The study aimed to test the feasibility and tolerability of structured moderate-intensity 12-week physical exercise program for adults with ADHD, as a prelude to an adequately powered RCT which includes long-term follow-up. Materials and methods Fourteen adults with ADHD were recruited, 9 randomized to an intervention group and 5 to a control group. The intervention group received physiotherapist-led 50-minute mixed exercise program, three times a week for 12 weeks, and the control group treatment as usual. Participants were assessed at baseline and after 6 and 12 weeks using clinical and physical evaluations, self-rating questionnaires, and functional magnetic resonance imaging (fMRI) together with paradigms that tested attention, impulsivity and emotion regulation. Results Three participants (21%) dropped out shortly after inclusion before receiving any intervention, while roughly 80% completed the intervention according to protocol. One participant from the intervention group participated in less than 60% of treatment sessions, and one who had done baseline fMRI was unwilling to do post-intervention imaging. Four participants in the intervention group (67%) reported increased stress in prioritizing the intervention due to time-management difficulties. Overall, consistent trends were observed that indicated the feasibility and potential benefits of the intervention on core ADHD symptoms, quality of life, body awareness, sleep and cognitive functioning. Conclusion Physiotherapist-led twelve-week regular physical exercise is a feasible and potentially beneficial intervention for adults with ADHD. There was a 20% drop-out initially and 67% of those who completed the intervention reported stress with time management difficulties due to participation. A third arm was thus added to the planned RCT where cognitive intervention administered by an occupational therapist will be given together with physical exercise. Clinical Trial Registration:https://clinicaltrials.gov, identifier NCT05049239.